Approach to imitate maneuvering of lunar roving vehicle under lunar gravity using a terrestrial vehicle. (September 2015) - Liang, Zhongchao; Gao, Haibo; Ding, Liang; Deng, Zongquan
Abstract: A lunar roving vehicle (LRV) is an important and indispensable detection tool that can not only transport astronauts a long distance from the lunar module but also ensures their safety when moving around the lunar surface. Thus, it is very important to train astronauts to drive the LRV on Earth. However, astronauts will experience different properties and driving sensations for the same vehicle owing to the difference in the gravities of Earth and the Moon. Thus, it is hard to train them on Earth using a normal LRV. Therefore, an approach is used to produce a vehicle that has the same steering properties and driving sensations as the LRV on the lunar surface. This approach involves a control algorithm that is developed in this paper using the H ∞ control theory. The math calculation and visual simulation results show that a four-wheel steering imitating LRV, which uses an imitating control algorithm, with either a higher stiffness torsion bar spring or lower payload than the LRV has a high imitation accuracy for the yaw speed, slip angle, and lateral acceleration at the driver's position. Finally, a highly accurate approach for imitating the steering of an LRV on the lunar surface has been realized, which lays the foundation for training astronauts to drive an LRV.